Vegetation responses to abrupt climatic changes during the Last Interglacial Complex (Marine Isotope Stage 5) at Tenaghi Philippon, NE Greece. (15th December 2016) - Milner, A.M.; Roucoux, K.H.; Collier, R.E.L.; Müller, U.C.; Pross, J.; Tzedakis, P.C.
Abstract: The discovery that climate variability during the Last Glacial shifted rapidly between climate states has intensified efforts to understand the distribution, timing and impact of abrupt climate change under a wide range of boundary conditions. In contribution to this, we investigate the nature of abrupt environmental changes in terrestrial settings of the Mediterranean region during the Last Interglacial Complex (Marine Isotope Stage [MIS] 5) and explore the relationships of these changes to high-latitude climate events. We present a new, temporally highly resolved (mean: 170 years) pollen record for the Last Interglacial Complex from Tenaghi Philippon, north-east Greece. The new pollen record, which spans the interval from 130, 000 to 65, 000 years ago, forms part of an exceptionally long polleniferous sediment archive covering the last 1.35 million years. The pollen data reveal an interglacial followed by alternating forest and steppe phases representing the interstadials and stadials of the Early Glacial. Superimposed on these millennial-scale changes is evidence of persistent sub-millennial-scale variability. We identify ten high-amplitude abrupt events in the pollen record, characterised by rapid contractions of closed forest to open steppe environment and interpreted to indicate major changes in moisture availability and temperature. The contractions in forest cover on millennial timescales appear associated with cooling events in the Mediterranean Sea, North Atlantic and Greenland regions, linked to the Dansgaard-Oeschger (DO) cycles of the Early Glacial. On sub-millennial timescales, the pattern of changes in forest cover at Tenaghi Philippon display a structure similar to the pattern of short-lived precursor and rebound-type events detected in the Greenland ice-core record. Our findings indicate that persistent, high-amplitude environmental variability occurred throughout the Early Glacial, on both millennial and submillennial timescales. Furthermore, the similarity of the pattern of change between Tenaghi Philippon and Greenland on sub-millennial timescales suggests that teleconnections between the high-latitudes and the Mediterranean region operate on sub-millennial timescales and that some terrestrial archives, such as Tenaghi Philippon, are particularly sensitive recorders of these abrupt climate changes. Highlights: Centennial-scale climate variability is detected throughout MIS 5 in NE Greece. Precursor/rebound events detected in Greenland are also seen at Tenaghi Philippon. Mediterranean vegetation variability corresponds to supra-regional climate variability. Close coupling between North Atlantic, Greenland, Mediterranean climate variability.